ANALISIS KESULITAN GURU DALAM IMPLEMENTASI KURIKULUM 2013 DI SDN 1 SIKUR - Hasni Hasni; Nassarudin Nassarudin; Awal Nur Kholifatur Rosyidah; Baiq Niswatul Khair (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2022)
The purpose of this study was to determine the difficulties experienced by teacher in implementing the 2013 curriculum. The research uses descriptive research with a qualitative approach. Data collection using interviews and documentation. Data were analyzed through data reduction, data presentation, and drawing conclusions. The subjects in this study were all teachers in SDN 1 Sikur. Based on the result of the analysis, it was found that the difficulties experienced by teachers at SDN 1 Sikur, among others is complicated assessment, the appication of a scientific approach, especially in reasoning and communicating, was not carried out properly, the difficulty of combining various subjects into one integrated theme, and the lack of fasilities and infrastructure. Efforts made to overcome these difficulties include participating in training/workshop on the implementation of the curriculum 2013, sharing information with colleagues or professions regarding the implementation of the curriculum 2013, working on student assessments in between non teaching schedules.